2019
DOI: 10.1002/pi.5779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different compatibilizers on environmentally friendly composites from poly(lactic acid) and diatomaceous earth

Abstract: Environmentally friendly composites from poly(lactic acid) (PLA) and diatomaceous earth (DE) were successfully manufactured by extrusion, followed by injection moulding. DE was used as a filler; several compatibilizer/coupling agents, namely (3‐glycidyloxypropyl)trimethoxysilane, epoxy styrene acrylic oligomer and maleinized linseed oil, were used to improve polymer–filler interactions. Mechanical characterization was carried out by standard tensile, impact and hardness tests while morphological characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…Comparative TGA thermograms of the neat PLA piece and the PLA pieces obtained after different reprocessing cycles are displayed in Figure 5. As expected, all samples (from PLA0 to PLA6) showed a one-step degradation process [76], as one can see in Figure 5a. It is worthy to note that several works have suggested that PLA decomposes in a two-step process when the thermogravimetric analysis is carried out under oxygen atmosphere [77], but it does not have any influence on this analysis since this induces thermo-oxidative degradation.…”
Section: Piecesupporting
confidence: 81%
“…Comparative TGA thermograms of the neat PLA piece and the PLA pieces obtained after different reprocessing cycles are displayed in Figure 5. As expected, all samples (from PLA0 to PLA6) showed a one-step degradation process [76], as one can see in Figure 5a. It is worthy to note that several works have suggested that PLA decomposes in a two-step process when the thermogravimetric analysis is carried out under oxygen atmosphere [77], but it does not have any influence on this analysis since this induces thermo-oxidative degradation.…”
Section: Piecesupporting
confidence: 81%
“…This is consistent with the above-reported effect of mechanical reinforcement of PLA by the lignocellulosic fibers. Similar remarkable increases in stiffness for natural filler-reinforced polymer composites have been reported previously [22,48,56]. The reinforcing effect was more pronounced after the glass transition region, in which the G value measured at 75 • C increased from 2.2.…”
Section: Thermomechanical Properties Of the Green Composite Piecessupporting
confidence: 87%
“…After this, the silanized FFs were removed from the bath and dried in a stove at 50 • C for 2 days. The concentration of the glycidyl-silane reactive coupling agent was selected based on our previous studies [56][57][58].…”
Section: Pretreatment Of the Flaxseed Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent investigations have revealed the interesting plasticization effect of maleinized vegetable oils in some polymers such as poly(lactic acid)—PLA—to increase chain mobility [1,25], but in general, there are few research works on the potential of these biobased materials as additive in plastic formulations. In addition to the plasticization effect of maleinized linseed oil (MLO) on PLA, it has been corroborated the coupling/compatibilizing effect of MLO on PLA composites with diatomaceous earth [26]. For this reason, MLO stands out as an alternative to traditional compatibilizers in the food packaging industry and, in particular, in active packaging, as diatomaceous earth particles are highly porous structures that can be loaded with antioxidants that can be released in a controlled way to increase the shelf life of a product.…”
Section: Introductionmentioning
confidence: 99%